Does asymptomatic generalized joint hypermobility influence musculotendinous extensibility and knee joint proprioception? - Chaiparinya, Pawan; Boonyong, Sujitra; Gaogasigam, Chitanongk (Chulalongkorn Medical Journal, 2024)
Background: It is unclear whether generalized joint hypermobility (GJH) influences the musculotendinous unit (MTU) extensibility or proprioception of the knee joint in individuals with asymptomatic GJH. Objectives: This study aimed to compare the quadriceps and hamstring MTU length as well as knee joint force sense (FS) and joint position sense (JPS) between individuals with asymptomatic GJH and non-GJH controls. Methods: Thirty-two female subjects were recruited, with 16 subjects in the GJH and non-GJH groups. The angles measured from modified prone knee bend (mPKB) and straight leg raising (SLR) tests were used to identify the quadriceps and hamstrings MTU extensibility using photographic-based angle measurements. The FS of the quadriceps and hamstrings and the JPS of the knee joint were assessed via ipsilateral angle and force-matching tasks, respectively. The results from the GJH and non-GJH groups were compared using unpaired t - tests or chi-square tests based on the distribution of the data. Results: The results indicated that the angles measured by the mPKB and SLR tests were not significantly different between the two groups. Furthermore, neither FS nor JPS differed between the GJH group and their peers. Conclusion: The asymptomatic GJH individuals did not show signs of hyperextensibility of the quadriceps or hamstring muscles. Moreover, the ability to perceive muscle force and the joint position of the knee joint were well preserved.